Analysis of the Role of Lightning Activity in Triggering Forest Fires in Nepal - Gyawali, Shriyog Sharma; Bhusal, Ramji Jaisi; Sharma, Shriram (Amrit Research Journal, 2024)
Forest fires have emerged as a significant and pressing issue in Nepal, jeopardizing its natural ecosystems, biodiversity, and communities. While human activities have been traditionally linked to these fires, this study explores the potential impact of lightning strikes, a natural factor that could contribute significantly to the problem. Using data from Vaisala's Global Lightning Dataset (GLD 360) and the Moderate Resolution Imaging Spectroradiometer (MODIS) dataset, we investigate the relationship between lightning strikes and forest fires over the five years’ period from 2015 to 2019. Advanced tools like ARC GIS and Python are employed for analysis. Preliminary findings indicate a noteworthy correlation, particularly during the pre-monsoon season. This investigation shows an interesting fact that positive lightning strokes are more likely to initiate forest fire as compared to their negative counter parts. This research offers a fresh perspective on lightning-induced forest fires in Nepal, paving the way for targeted fire management strategies and further investigation into lightning ignition mechanisms.